2018
DOI: 10.1021/acs.est.8b05035
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion and Chronic Effects of Car Tire Tread Particles on Freshwater Benthic Macroinvertebrates

Abstract: Micronized particles released from car tires have been found to contribute substantially to microplastic pollution, triggering the need to evaluate their effects on biota. In the present study, four freshwater benthic macroinvertebrates were exposed for 28 days to tread particles (TP; 10–586 μm) made from used car tires at concentrations of 0, 0.1, 0.3, 1, 3, and 10% sediment dry weight. No adverse effects were found on the survival, growth, and feeding rate of Gammarus pulex and Asellus aquaticus, the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 59 publications
12
81
0
Order By: Relevance
“…Secondary microplastics are derived from large plastic items being degraded into small plastic fragments upon exposure to the environment [52]. The largest proportion of these particles is derived from laundering textiles with mixed synthetic fibers [16] and the friction of car tires [17,18]. Secondary microplastics from synthetic textiles in garments are the major type of microplastics [53,54].…”
Section: Routes Of Plastic Micromaterials and Nanomaterials Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary microplastics are derived from large plastic items being degraded into small plastic fragments upon exposure to the environment [52]. The largest proportion of these particles is derived from laundering textiles with mixed synthetic fibers [16] and the friction of car tires [17,18]. Secondary microplastics from synthetic textiles in garments are the major type of microplastics [53,54].…”
Section: Routes Of Plastic Micromaterials and Nanomaterials Pollutionmentioning
confidence: 99%
“…The plastic debris in aquatic environments is fragmented into smaller pieces by ultraviolet light and biodegraded plastic forms microplastics and nanoplastics [13][14][15]. However, the largest proportion of microplastics and nanoplastics is generated from the laundering of textiles with mixed synthetic fibers [16] and the friction of the tires of moving cars [17,18]. These microplastics and nanoplastics have unclear effects on organismal systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of CRG particles by marine organisms is known to occur (Redondo-Hasselerharm et al, 2018;Khan et al, 2019), leading to potential exposure through leaching during gut transit. However, exposure of marine organisms to additive chemicals in CRG is likely to be more widespread through leaching to the aqueous phase, especially as some of these additives exhibit persistency in the environment (Halle et al, 2020).…”
Section: What Are the Drivers Of Crg Leachate Toxicity?mentioning
confidence: 99%
“…Laboratory studies with cladocerans (Daphnia magna) and algae (Pseudokirchneriella subcapitata) indicated the major toxic constituent in freshwater leachates is Zn, with minor contributions from organic compounds (Gualtieri et al, 2005;. A recent study reported only small fractions of the heavy metals and PAHs present were bioavailable for freshwater benthic macroinvertebrates (Redondo-Hasselerharm et al, 2018). However, many urban areas are located on the coast, making the marine environment an additional likely sink for CRG as it is transported through the environment.…”
Section: Introductionmentioning
confidence: 99%
“…com.). The bioavailability of Zn from TRWP/car tyre dust is low (see measurements of Redondo-Hasselerharm et al, 2018). Therefore, addressing zinc within the risk assessment of TRWP does not seem to be relevant.…”
mentioning
confidence: 99%